PENGEMBANGAN BAHAN AJAR DIGITAL MATEMATIKA SMA KELAS X BERORIENTASI HOTS - I Kadek Surya Atmaja; I Komang Sukendra; I Wayan Widana (Widyadari : Jurnal Pendidikan, 2021)
HOTS learning is learning in the cognitive domain of analyzing, evaluating, and creating. This study aims to determine the development steps and quality of digital mathematics teaching materials for class X SMA HOTS oriented on the material of a three-variable linear equation system. This research and development procedure uses an adaptation of the Plomp model, with the following steps: initial investigation, design, realization/construction, and test, evaluation and revision. Sources of research data are validators and high school mathematics teachers. Research data collection techniques using a questionnaire. The results of the initial validity test were declared "valid", with a material validity value of 0.72, language validity 0.92, and media validity 0.87. The results of the final stage of the validity test were declared "valid", with a validity value of 0.95. In the quality test, HOTS-oriented digital teaching materials were declared to have "good quality", with the result that all indicators on aspects of content, presentation, language, and media obtained an average score in the range of 9-10 on the Thurstone scale, the value of the interquartile range which is small below 2 and the mode value is close to 11 on the Thurstone scale.